Environmental costs and compliance with standards: factors of sustainable development of the agricultural sector - Berdimurat, N.; Dauletova , G.; Akhmetova S.О.; Orynbassarova А.А.; Aimkulov , R.A.; Beketova , K.N. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this study is to analyze environmental costs and their impact on compliance with environmental standards in the agricultural sector, as well as to assess their role in ensuring the sustain able development of the industry. Methods: The study is based on the analysis of the regulatory framework, statistical data and empirical research. A comparative analysis of environmental compliance practices in different regions has been ap plied. Both qualitative and quantitative methods are used, including the assessment of environmental costs and the impact of compliance on the sustainable development of the agricultural sector. Results: The results of the study showed that compliance with environmental standards in the agricultural sector contributes to reducing environmental costs and improving the sustainability of the industry. The key factors influencing the effectiveness of the implementation of environmental standards have been identified, as well as barriers to full compliance with the standards. The assessment showed the positive impact of environmental responsibility on the competitiveness of agricultural enterprises and on the long-term sustain ability of the agricultural sector. Conclusions: Compliance with environmental standards in the agricultural sector contributes to the sustainable development of the industry, reducing environmental costs and improving its competitiveness. Measures are needed to remove barriers to full compliance with standards, including support for innovative technologies and increased controls. The introduction of environmentally sustainable practices has long-term benefits for agriculture, ensuring a harmonious combination of economic efficiency and environmental responsibility.